Epidemiologic Study of Pediatric Uveitis and its Ophthalmic Complications Using the Korean National Health Insurance Claim Database - Hong, Eun Hee; Kim, Jiyeong; Kang, Min Ho; Park, Sung Who; Tran, Anh Ngoc Tram; Karaca, Irmak; Akhavanrezayat, Amir; Or, Chi Mong Christopher; Thng, Zheng Xian; Bromeo, Albert John; Khatri, Anadi; Do, Diana; et al. (American journal of ophthalmology, 2025)
To investigate the incidence and ophthalmic complications of pediatric uveitis using the Korean National Health Insurance (NHI) Service database. Nationwide population-based longitudinal cohort study. This study used the NHI database from 2005 to 2021 and included individuals <18 years of age diagnosed with uveitis on at least three separate visits between 2010 and 2014, with a five-year wash-out period and a seven-year follow-up period. All uveitis cases were classified as either anterior or nonanterior on the basis of the diagnostic code. The occurrence of ophthalmic complications during the follow-up period, and the systemic and socioeconomic associations between pediatric uveitis and its ophthalmic complications were investigated. We obtained the incidence of total, anterior, and nonanterior pediatric uveitis between 2010 and 2014; the percentage of ophthalmic complications during the follow-up period; and hazard ratios for ophthalmic complications of anterior and nonanterior uveitis. A total of 9495 cases of pediatric uveitis (8734 cases with anterior and 761 with nonanterior uveitis) were identified, with an average annual incidence (per 10 000 children) of total, anterior, and nonanterior uveitis being 2.0, 1.8, and 0.2, respectively. The most common complications were glaucoma or presumed ocular hypertension, macular disease, and amblyopia. Patients with nonanterior uveitis had a significantly higher risk of ophthalmic complications including retinal detachment, cataract, amblyopia, and glaucoma or presumed ocular hypertension than those with anterior uveitis. This nationwide analysis of pediatric uveitis in South Korea revealed an average incidence of 2.0 per 10 000 children, highlighting the higher risks of ophthalmic complications associated with nonanterior uveitis.